Fifty years of European history through the Lens of Computational Linguistics: the De Gasperi Project - Rachele Sprugnoli (Accademia University Press, 2016)
In 2013 a collaboration was started between the Digital Humanities research unit and the Italian-German Historical institute at Fondazione Bruno Kessler, whose goal was to develop tools and strategies to give new insight into the public documents written by Alcide De Gasperi. Through the analysis of textual occurrences, semantic structures, and temporal patterns, the project, ending in 2017, has investigated the formation and evolution of De Gasperi’s political action and the rhetorical discourse that accompanied its developments. Research of this kind has contributed to better understanding De Gasperi’s thoughts, the links between his language and his political views and culture, and the instruments of his communication. On the other hand, it allows the design and development of automated research tools for the political domain. This is a distinctly interdisciplinary research project, in which historical inquiry interacts with methods of linguistic analysis and with information and communication technologies.